Synthesis of copper-64 and technetium-99M labeled oligonucleotides with macrocyclic ligands - Wagner, Sven; Eisenhut, Michael; Eritja, Ramon; Oberdorfer, Franz (Nucleosides & nucleotides, 1997)
An efficient procedure for the preparation of oligonucleotides carrying a mono-N-substituted azamacrocycle and its radiolabeled complex with Cu-64 and Tc-99m is reported. The new derivatives are of potential interest for Positron Emission Tomography and Single Photon Emission Tomography.
Elektronische Reproduktion der Druck-Ausgabe 16. August 2006
Gesehen am 09.12.2024